Atypical Nevus Sebaceus at an Unusual Location Treated with Carbon Dioxide Laser: A Case Report - Sutedja EK; Mareta S; Sutedja E; Ruchiatan K (Dove Medical Press, 2022)
Eva Krishna Sutedja, Shela Mareta, Endang Sutedja, Kartika Ruchiatan Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran, Dr. Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Eva Krishna Sutedja, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62 812 201 4300, Email evakrishna@yahoo.comAbstract: Nevus sebaceus (NS) or organoid nevus is an epidermal nevus comprising predominantly sebaceous glands with a prevalence of approximately 0.3% of the newborns. The initial clinical manifestations of NS are single or less commonly multiple yellowish patches with overlying alopecia, usually confined to the scalp. However, it can also appear on the face, preauricular area, and the neck. During puberty, skin lesions will turn into round or linear verrucous plaques accompanied with an increase in number due to the influence of androgens. As they progress, about 20% of the NS cases might turn into secondary tumors which can be benign or malignant (in 2.5% cases). NS can manifest as atypical lesions and may also arise on areas other than its predilection sites. A case of a lesion presented on an atypical location of an 18-year-old male patient treated with carbon dioxide (CO2) laser was reported. Physical examination revealed skin-colored and blackish-brown papules arranged in groups on the left side of the patient's chest. Histopathological examination on a sample taken from one of the skin lesions on the chest showed hyperkeratosis, acanthosis, papillomatosis, and sebaceous hyperplasia, confirming the diagnosis of NS. The patient was treated with CO2 laser, and clinical improvements were observed. Histopathological examination of NS is not routinely performed; however, it should be carried out when the lesion is atypical and presented at an unusual location, or there is a suspicion of malignancy.Keywords: atypical lesion, nevus sebaceus, unusual location, carbon dioxide laser